LIngvokulturologichesky’s features of the analysis of the concept “time” in different languages - Baigaltinova, М.; Dauen, D. B. (Journal of Oriental Studies, 2016)
The relevance of this study is determined by the lack of elaboration of the theory and practice of the comparative study of existingconcepts from the different languages.In the pictures of the world of many ethno-linguistic communities, as are the basis, the foundation of the entire world. The conceptof время in the Russian language, time/tense in English, shíjiān in the Chinese language by right included in the number of such concepts,representing one of the load-bearing structures of the image of the world.